Acylated Derivatives of Streptokinase-Plasminogen Activator Complex as Thrombolytic Agents in a Dog Model of Aged Venous Thrombosis - Dupe, R J; Green, J; Smith, R A G (Thrombosis and Haemostasis, 1985)
A procedure is decribed for the establishment of experimental clots, aged in vivo for 72 hr, in the jugular vein of beagle dogs. Two acylated derivatives of streptokinase-human (lys) plasminogen activator complex with greatly differing deacylation rates under physiological conditions were compared as thrombolytic agents in the model. These were BRL 26921 (deacylation halflife, 40 min) and BRL 33575 (deacylation half-life c. 17hr). The pharmacokinetic clearance rate of BRL 33575 from the circulation was studied and gave a clearance half-life of about 7 hr. BRL 33575 was found to be the superior agent in lysing 72 hr aged clots, being effective at a single bolus dose of 420 μg/kg or in three equal divided doses of 140 μg/kg given at 12 hr intervals. The single dose regime gave moderate systemic plasminogen activation, and the effect was significantly reduced with the divided dose regime. Infusion of freshly formed streptokinasehuman plasminogen activator complex at 420 μg/kg over 15 hr gave little thrombolysis despite marked systemic plasminogen activation.
Keywords: Thrombolysis; Streptokinase-plasmin; Acylated ativators; Dog; Aged venous clots